Variação espacial e temporal no uso do habitat por jaguatirica (Leopardus pardalis) em florestas de terra firme da Amazônia Central, Brasil - Pimentel, Victor Siqueira (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
The distribution of mammals in different environments shows the influence of biotic and abiotic factors on the way they use such habitats. Seasonality can have a great impact on the variation of such factors. Habitat structure and resource availability are especially relevant aspects for the persistence of carnivores in a given area. Consequently, we evaluated the effect of environmental factors on spatial and temporal variation of ocelot occurrence in terra firme environments (paleo-várzea) in Central Amazon. Additionally, we then sought to understand the relationship between ocelot occurrence and occurence of potential prey, distance from traditional communities, distance from ecotones with flooded areas and forest cover. We conducted the study using camera traps arranged in six blocks of terra firme for 132 days across two annual seasons, those of high and low water levels. We used 50 cameras in each block, with a total sampling effort of 6,600 traps*day. Our results showed a temporal variation in the use of potential prey species and no influence of the landscape variables. We conclude that biotic interactions were the main factors determining occurence of ocelots in the Central Amazon terra firme forests studied.
Keywords: Jaguatirica; Habitat; Floresta de Terra Firme